Akibat Hukum Kawin Lari Berdasarkan Hukum Islam Dan UU Perkawinan (Studi Kasus Kec. Tolinggula) - Kaunang, Alfian; Dungga, Wenny Almoravid; Bakung, Dolot Alhasni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Marriage is something that is sacred and contains the value of worship, in line with the greatness and how high the value of marriage is, in the hadith it is stated; "a person who does marriage is the same as doing half worship". However, even though Islam has provided clear rules regarding marriage, in reality there are still many different implementations or practices of marriage. This happens because the background is the plurality of Muslims with their customs and culture which are so patterned and varied. In addition, the logic of Indonesian Muslims between one region and tribe is also quite different, this condition can lead to differences, both in terms of implementation, use of names or terms. The legal position of elopement according to the Marriage Law in Indonesia is that basically elopement is actually still in the category of unregistered marriage because the implementation is carried out in secret or in secret, it's just that the guardian of the marriage in this case is an illegitimate guardian, as well as witnesses and registrars the legal consequences of elopement according to the Marriage Law in Indonesia are legal actions and have legal consequences because elopement always encounters problems in state administration not obtaining a marriage book from the KUA and the state does not recognize elopement. Elopement does not get public services in government agencies because it is carried out illegally due to the absence of a legal guardian, so all forms of legal relations related to marriage administration cannot be carried out. In addition, if the woman's parents and family object to the elopement case experienced by her child, then in accordance with the provisions By law, the woman's parents and family can report it to the authorities and be processed legally.